(NpOLIFONIQs (NTEORIQ(B.(Nu^EBNIKs - (Ns(B.(Ns(B.(NsKREBKOWs ((NmOSKWAs (N`RAJTs, 2025)
(Nw U^EBNIKE SODERVITSQ OB[IRNYJ TEORITI^ESKIJ MATERIAL OBOB]A@]IJ W SEBE MNOGOLETNIJ NAU^NYJ I PEDAGOGI^ESKIJ OPYT AWTORAs
Keywords: (NtEORIQ(B.s